Digital Entrepreneurial Strategy (Des) as A New Concept Business Strategy from offline to online post Pandemic Covid - 19 - Dipan Diandra (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Entrepreneurship is business activity to make a profit. in contrast to this view, entrepreneurship during and post covid-19 entering into a new wave of business called digital business transform whishings shifted the market behavior from offline to online. this study aplows the rigor of literature and explore empirical analysis based on entrantreenurial strategy. this study aims to leageage firmance and as partation of faceing society 5.0. entrepreneurial orientation (eo) concept and digital entrepreneurial strategy (des) are analyzed to explore larger market with unlimited time and distance. this research coud become a reference for entrrepreens in ining business and making a recec decor digital dra.